Pemberdayaan Perempuan Sebagai Upaya Pembangunan Desa - Handrianus Vianey Melin Wula; Melkianus Suni (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2020)
ABSTRACT This study aims to look at women's empowerment activities in Letmafo Village, Insana Tengah Subdistrict, North Central Timor Regency, which is a district directly adjacent to the Democratic Republic of Timor Leste, through the weaving group with the target of research on the group of weaving craftsmen 'Teon Tabua'. in Letmafo Village. The research method used in this research is to use qualitative methods. The results of this research show that the development process in Letmafo village, women former migrant workers participate in development through empowerment activities of the 'Teon Tabua' weaving group with a process of opportunities given to the community, the community's willingness to support, and the community's ability to calculate in the empowerment program carried out in the village, the result is to support household income. The conclusion of this research is that the opportunity, willingness, and ability to participate in village development have been carried out by women who are determined by their mentality to build or improve their lives with their interactions in the empowerment group of 'Teon Tabua' weaving tenun. Keywords: Village Development, Women Empowerment.